Assessing the Feasibility of Cogeneration Retrofit for Heating and Electricity Demands in Marine Diesel Engines - Xianglong Liu; Hao Yang; Zhao Feng; Guang Hu; Zhi Zeng (International Transactions on Electrical Energy Systems)
In the marine engineering industry, turbocharged diesel engines are often used to generate electricity, and hot oil can be extracted after generating electricity. However, marine diesel engine heat recovery can be distinguished from gas heat recovery for turbocharged and nonturbocharged diesel engine systems. The ideal air model Brayton cycle is used to evaluate the feasibility of turbocharged/nonturbocharged cogeneration retrofits in turbocharged diesel engine systems, and the paper is designed to evaluate the effect of pressure and temperature and cooling ratio of exergy efficiency. The results show that the performance of turbocharged and nonturbocharged work increases with increasing pressure ratio until it reaches a maximum value and decreases with increasing pressure ratio at a constant temperature. If an electric generator is selected first, the heat recovery after the turbocharger can be used to improve the contract for heating and electricity needs. While the exergy efficiency is selected priorly, cogeneration retrofit for heating and electricity demands can be used for heat recovery without the turbocharger system.